Emerging “third space” and students’ identities in a heritage language classroom - Vorobeva, Polina (2018)
The main goal of the research was to examine the emerging third space in the heritage language classroom of bilingual students who are proficient in Russian and Finnish languages. The study was implemented as an action research within the context of supplementary evening classes for students of the ages 12 to 16. In order to carry out the research one 45 minutes lesson was video recorded, transcribed and peculiar pieces of the lesson interaction were translated from Russian into English. Before going into the field, the questionnaires were filled in by the students. Questionnaires provided an overview on the whole classroom as well as it included the information concerning students’ language use. The methodology of the research is framed by qualitative method, such as mediated discourse analysis. The findings of the research indicated that third space can facilitate learning in heritage language classroom. Five types of discourses which formed the third space appeared in the research results. Among those are: discourse of hobbies, discourse of the foreigner abroad, discourse of childhood, discourse plans vs. expectations and discourse of culture. Additionally, the research showed that third space can be successfully created in the heritage language classroom with the help of a graphic novel, however it has a potential to be developed further in order to make stronger connections between every day and academic funds of knowledge.